Establish The Policy Target to Reduce Stunting Among Indonesian Toddlers with Single Mothers - Sandra, Christyana; Sandra, Ratna Dwi Wulandari; Laksono, Agung Dwi; Ningsi, Ningsi; Tumaji, Tumaji (Universitas Negeri Semarang (UNNES) in cooperation with the Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2025)
Single mothers bear two significant burdens: domestic responsibilities and earning an income. The role of a mother determines the nutritional status of a toddler. Until now, policies about stunting have not focused on specific target areas. The study aims to establish a policy target for reducing stunting among Indonesian toddlers with single mothers. The cross-sectional study examined 5,387 toddlers. Eight independent factors were considered: place of residence, mother’s age, occupation, education, socioeconomic status, antenatal care (ANC), children’s age, and sex. A binary logistic regression test was used for data analysis. 20.0% of Indonesian toddlers who had single mothers were stunted. Rural youths were 1.171 times more likely to be stunted (95%CI 1.149-1.192). All maternal ages were more likely to have stunted kids than ≥45. Lower education increases the risk of stunted toddlers. Unemployed mothers were 1.170 times more likely to have stunted kids (95%CI 1.148-1.192). The wealthier the household, the less likely the under-fives are to be stunted. Mothers without ANC were 1.194 times more likely to have stunted toddlers (95%CI 1.116-1.278). Toddlers were more likely than infants (0-11 months) to be stunted, and girls had a higher risk of stunting. The policy targeted rural areas, low-income families with young, uneducated, unemployed mothers, no ANC, older toddlers, and girls.